Understanding knowledge sharing through the working practices. Issue 4 (28th September 2020) - Agrifoglio, Rocco; Briganti, Paola; Varriale, Luisa; Metallo, Concetta; Ferrara, Maria
Abstract : Purpose: Building upon the practice-based framework, this paper aims to focus on working practices for understanding how knowledge is transferred among health-care professionals within hospitals. Design/methodology/approach: Using an ethnographic and interpretative approach, the authors conducted preliminary research based on a quali-quantitative methodology within one of the largest hospitals in Southern Italy. Findings: This study allowed to achieve several results that could be significant and relevant within the health-care sector. First, this paper identified some of the main working practices and their associated activities in health care. Moreover, this paper identified the main organizational forms and/or tools enabling hospital personnel to share and learn the various types of knowledge for each of the prior identified practices. Practical implications: Hospital managers should develop strategies and policies that take into account the nature and typology of knowledge-sharing processes among health-care professionals in terms of practices. Originality/value: The paper contributes to practice-based studies identifying identified some of the main working practices, as well as the main tools for sharing and learning of the various types of knowledge.